EPIDEMIOLOGICAL TRENDS OF MEASLES AMONG CHILDREN AND EVALUATION OF THE EFFECTIVENESS OF PREVENTIVE MEASURES (Innovate Conferences, 2025)
Measles remains one of the most contagious and socially significant viral infections of childhood, continuing to pose a serious public health challenge despite the availability of effective vaccines. According to the World Health Organization (WHO), recent years have witnessed a resurgence of measles cases in various regions of the world, including areas that previously maintained stable epidemiological control. The resurgence is largely attributed to declining herd immunity, insufficient vaccination coverage, and delays in the timely implementation of routine immunization and revaccination programs.